Pengaruh Current Ratio, Debt To Equity Ratio, Total Asset Turnover terhadap Return on Assets pada Perusahaan Sub Sektor Kosmetik dan Barang Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia - Dedek Kurniawan Gultom; Mukhritazia Manurung; Roni Parlindungan Sipahutar (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, Simultaneous Total Asset Turnover on Return on Assets. The research approach used in this study is an associative approach. The population in this study is the cosmetics and household goods sub-sector companies listed on the Indonesia Stock Exchange for the period 2012-2017, amounting to 6 companies. The sampling technique in this study was determined by purposive sampling, so for the withdrawal of samples in this study there were 5 companies in the cosmetic and household goods sub-sector. Data analysis techniques in this study used multiple regression analysis. The results of this study indicate that the Current ratio has no significant effect on Return On Assets. Debt to Equity Ratio has a significant effect on Return On Assets. Total Asset Turnover has no significant effect on Return On Assets. Simultaneously the effect of Current Ratio, Debt to Equity Ratio, Total Asset Turnover simultaneously is a significant influence on Return on Assets